Formation of methodical foundations for assessingthe innovative development potential of an industrial enterprise - Chukurna, O.; Niekrasova, L.; Dobrianska, N.; Izmaylov, Ya.; Shkrabak, I. V.; Ingram, K.; Шкрабак, І. В. (Національний гірничий університет, 2020)
Formation of methodological foundations for assessing the innovative development potential of an industrial enterprise. The rationale for the use of a comprehensive system of indicators that will allow conducting assessment of the ability of its innovative development, identifying the risks and threats that affect the innovative activity of the enterprise. Definition of an approach to assessing not only quantitative indicators, but also qualitative ones regarding the innovative development potential of an industrial enterprise.

Формування методичних засад оцінки потенціалу інноваційного розвитку промислового підприємства. Обґрунтування використання комплексної системи показників, що дозволять здійснити оцінку спроможності щодо інноваційного розвитку, визначити ризики та загрози, які впливають на інноваційну діяльність підприємства. Визначити підхід щодо оцінки не тільки кількісних, але й якісних показників щодо потенціалу інноваційного розвитку промислового підприємства.
Формування методичних засад оцінки потенціалу інноваційного розвитку промислового підприємства
Keywords: industrial enterprise; innovation assessment; multidimensional scaling; innovative potential; промислове підприємство; оцінка інновацій; багатомірне шкалування; інноваційний потенціал